Estudo de malhas amostrais em cafeicultura de precisão - Figueiredo, Vanessa Castro (2016)
The importance of coffee in the world economy is undeniable. It is one of the most valuable products marketed in the world, second only in value by oil. Its cultivation, processing, marketing, transportation and market provide millions of jobs worldwide. Producers, and directors are increasingly assuming the role of researchers producing their areas, acting directly on gathering information, interacting with new techniques and taking effective management decisions. The Precision Agriculture is a management system that came up with this objective to apply technological solutions that is slowly evolving to a more promising situation and that really shows potential and results. For the decision making becomes necessary knowledge of the spatial variability, a technique that requires representative field sampling are performed to approach the reality of most crop. Thus, the aim of this study was to apply precision agriculture techniques to identify the sampling grid that best characterize the spatial variability in terms of sampling points technically and economically feasible for coffee crops on plots of up to 100.0 ha. The experiment was conducted at Fazenda Três Pontas, municipality of Presidente Olegário/MG in three areas (112 ha, 50 ha and 26 ha) in the years 2014 and 2015. In the three areas studied were georeferenced 224, 100 and 50 points, respectively (average of 2.0 points/ha) from the mesh 1 were taken three meshes, the mesh 2 being (point 1/ha) 3 mesh (0.7/ha) and 4 mesh (0.5 point/ha). From this was made the collection of Fertility Soil data and productivity of coffee plantations for application of the methodology. In working conditions it can be concluded that the recommended mesh was the mesh one with the highest number of sampling points.